Metafísica e retorno às origens da Filosofia em Lima Vaz - Santos, Luiz Fernando dos (2019)
This dissertation aims to reflect the thinking of Lima Vaz demonstrating the itinerary that he goes through using his ability to think about his time by returning to the origins of Philosophy. Reflecting on the lima-vaz thinking that we try to think about the problems pointed out by him and indicate his diagnosis about his time. His hermeneutical analysis of modernity understands that it originates in the crisis of the thirteenth century and can be understood from Thomas Aquinas when he thinks about the ontic situation of man and gives primacy to existence, giving it the condition of being thought and reflected. In this way, by synthesizing Plato and Aristotle, he can suppress them, thus overcoming the essentialism which understood existence as unintelligible. In this sense, Lima Vaz argues that Philosophy is anamnesis and noesis, in other words, thinking about its historical trajectory is able to reinvent the problems that gave rise to it and offer answers. The restlessness that moves beings in search of knowledge is properly metaphysical, since it is able to recognize, like Plato, that the first navigation on the transient does not satisfy man, he is thrown with all his soul beyond the cave in search for the light of knowledge, and can accomplish such an object only if he is able to make the second navigation to the intelligible, in other words, to the subsistence esse. In this way, one can see in the reading of lima-vaz options by Plato, Aristotle, St. Augustine, Thomas Aquinas, and Hegel. It is thinking and reflecting on a metaphysics of esse that it judges to find the roots that have made the tree of modernity grow